2010
DOI: 10.46867/ijcp.2010.23.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Journal Publication Trends Regarding Cetaceans Found in Both Wild and Captive Environments: What do we Study and Where do we Publish?

Abstract: We would to extend a special thank to Mr. Alonzo Mendoza and Ms. Samantha Lopez for their help in locating and compiling additional sources for this study. Without their help and Ms. Monica Lackups' dedication, this study would not have been possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 1,212 publications
0
2
0
Order By: Relevance
“…Bottlenose dolphins have been in human care for more than 50 years, during which many aspects of their physiology, anatomy, health, behavior, acoustics, and cognition have been studied [ 12 , 13 , 14 ]. Research has indicated that the lifespan of bottlenose dolphins in managed care is now longer, on average, than bottlenose dolphins in the wild [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bottlenose dolphins have been in human care for more than 50 years, during which many aspects of their physiology, anatomy, health, behavior, acoustics, and cognition have been studied [ 12 , 13 , 14 ]. Research has indicated that the lifespan of bottlenose dolphins in managed care is now longer, on average, than bottlenose dolphins in the wild [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common bottlenose dolphins (Tursiops truncatus) are the most widely studied cetacean species, both visually and acoustically (Hill and Lackups, 2010), throughout the Mediterranean Sea due to their highly coastal distribution (Bearzi et al, 2008). According to the IUCN Red List, bottlenose dolphins have experienced a 30% decline in their population size since the 1940s in the Mediterranean Sea, while Adriatic populations declined by almost 50% in the latter half of the 20th century (Bearzi et al, 2004;Sackl et al, 2007;Bearzi et al, 2008;Bearzi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%